Subtly Manipulated Expression of ZmmiR156 in Tobacco Improves Drought and Salt Tolerance Without Changing the Architecture of Transgenic Plants - Kang, Tao; Yu, Chun-Yan; Liu, Yue; Song, Wei-Meng; Bao, Yan; Guo, Xiao-Tong; Li, Bei; Zhang, Hong-Xia (Frontiers in Plant Science, 2020)
Plants in the juvenile state are more tolerant to adverse conditions. Constitutive expression of MicroRNA156 (miR156) prolonged the juvenile phase and increased resistance to abiotic stress, but also affected the architecture of transgenic plants. In this study, we investigated the possibility of subtle manipulation of miR156 expression in flowering plants, with the goal to increase tolerance to abiotic stress without altering the normal growth and development of transgenic plants. Transgenic tobacco plants expressing ZmmiR156 from maize were generated, driven either by the cauliflower mosaic virus (CaMV) 35S promoter or the stress-inducible ZmRab17 promoter. Expression of ZmmiR156 led to improved drought and salt tolerance in both 35S::MIR156 and Rab17::MIR156 transgenic plants, as shown by more vigorous growth, greater biomass production and higher antioxidant enzyme expression after a long period of drought or salt treatment, when compared to wild type and transgenic vector control plants. However, constitutive expression of ZmmiR156 also resulted in retarded growth, increased branching and delayed flowering of transgenic plants. These undesirable developmental changes could be mitigated by using the stress-inducible ZmRab17 promoter. Furthermore, under drought or salt stress conditions, expression of ZmmiR156 reduced the transcript level of NtSPL2 and NtSPL9, the genes potentially targeted by ZmmiR156, as well as that of CP1, CP2, and SAG12, the senescence-associated genes in tobacco. Collectively, our results indicate that ZmmiR156 can be temporally manipulated for the genetic improvement of plants resistant to various abiotic stresses.